ANALISIS MINAT PENGGUNAAN INFORMASI AKUNTANSI PADA USAHA KECIL DAN MENENGAH DI PURWOKERTO - Pujiati *; Bambang Setyobudi Irianto; Mafudi * (Jurnal Riset Akuntansi Soedirman (JRAS), 2022)
This study aimed to analyzing intention of use accounting information at small and medium enterpriseses in Purwokerto. The sample in this study using proportionate stratified random sampling technique as many as 80 small and medium enterpriseses in the field of trade, manufacturing and services. Data collection in this study using a questionnaire survey. The data collected were processed using partial least square analysis (PLS). The results of this study indicate that partial perceived usefulness and perceived ease of use positively affects the attitude of the use of accounting information on small and medium enterprises in Purwokerto. Partially attitudes, subjective norms, and perceived behavioral control positive influence on interest in the use of accounting information on small and medium businesses in Purwokerto.